How strongly are business cycles and financial cycles linked in the G7 countries? - Nikolaos Antonakakis; Max Breitenlechner; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
In this study we examine the dynamic interactions between credit growth and output growth using the spillover index approach of Diebold and Yilmaz (2012). Based on quarterly data on credit growth and GDP growth over the period 1957Q1-2012Q4 for the G7 countries we find that: i) spillovers between credit growth and GDP growth evolve rather heterogeneously over time and across countries, and increase during extreme economic events. ii) Spillovers between credit growth and GDP growth are of bidirectional nature, indicating bidirectional causation between the financial and real sectors. iii) In the period shorty before and on the onset of the global financial crisis, the link between credit growth and GDP growth becomes more pronounced. In particular, the financial sector plays a dominant role during the early stages of the crisis, while the real sector quickly takes over as the dominant source of spillovers. iv) Interestingly, credit growth in the US is the dominant transmitter of shocks internationally, and especially to other countries' real sectors in the run up period to (and during) the global financial crisis. Overall, our results suggest feedback effects between the financial and the real sectors that create rippling effects within and between the G7 countries during the global financial crisis.
Keywords: C32; E32; E44; E51; F42; 330; Business cycles; Financial cycles; Spillovers; Crisis; Recession